Minor plasma lipids modulate clotting factor activities and may affect thrombosis risk - Deguchi, Hiroshi (Res Pract Thromb Haemost, 2017)
ESSENTIALS: Circulating blood contains hundreds of lipids, many of which might influence blood coagulation. Recent discoveries about circulating lipids that can affect blood coagulation are reviewed. Minor abundance plasma lipids can modulate thrombin generation via direct effects on factor Xa. Variations in minor abundance plasma lipids can influence thrombin generation and thrombosis risk. ABSTRACT: Different minor abundance plasma lipids significantly influence thrombin generation in vitro and significant differences in such lipids are linked to risk for venous thrombosis. Some plasma sphingolipids including glucosylceramide, lyso‐sulfatide and sphingosine have anticoagulant properties whereas, conversely, some plasma phospholipid derivatives, including certain lyso‐phospholipids and ethanolamides, have procoagulant properties. Plasma metabolite profiling of venous thrombosis patients showed association of venous thrombosis with decreased plasma long‐chain acylcarntines, leading to discovery of their anticoagulant activity as inhibitors of factor Xa. Inhibition of factor Xa by acylcarnitines does not require the protein's Gla‐domain, emphasizing an expanded framework for the paradigm for lipid‐clotting factor interactions. Overall, whether by genetics or environment, alterations in the dynamics of lipid metabolism linked to an altered lipidome may contribute to regulation of blood coagulation because imbalances between physiologic procoagulant and anticoagulant lipids may contribute to excessive thrombin generation that augments risk for thrombosis.